The role of open-pore film drainage systems in endoscopic vacuum therapy: current status and review of the literature: review article - Kouladouros, Konstantinos; Wichmann, Dörte; Loske, Gunnar (Visceral medicine, 2023)
Background: Endoscopic vacuum therapy (EVT) is an increasingly popular endoscopic technique used for the treatment of wall defects in the gastrointestinal tract. Open-pore film drainage (OFD) systems are a new addition to the armamentarium of EVT and have shown encouraging results in a wide spectrum of applications. The aim of this review is to summarize the current literature on the applications of OFD systems in the gastrointestinal tract. Summary: Open-pore film drainage (OFD) systems have been used for the treatment of several defects of the gastrointestinal tract. The small size and easy placement of these devices make them very useful, particularly for the treatment of defects that are small in size or difficult to reach. OFDs have been successfully used for both perforations and anastomotic leaks in various locations, with most reports focusing on the treatment of duodenal defects, although successful applications in the esophagus, stomach, and colon have also been reported. Lately, the role of OFDs in preemptive EVT has also been explored. Key Messages: OFD systems are easy to use, particularly for small defects and challenging localizations. The current literature, consisting mainly of small case series and case reports, shows encouraging results, but further prospective studies are needed to explore and verify the indications and technical aspects of this innovative method.
Gesehen am 08.02.2024